Non-invasive Renal Denervation: Update on External Ultrasound Approaches - Schmieder, Roland; Ott, Christian; Bramlage, Peter (Current Hypertension Reports, 2016)
In the last decade, intravenous renal denervation (RDN) has emerged as an alternative to pharmacological treatment in patients with resistant hypertension, but currently involves an invasive and technically challenging procedure. The Surround Sound(TM) system utilises externally delivered ultrasound to achieve RDN using a completely non-invasive, automated real-time tracking system coupled with a therapeutic delivery module thereby addressing these limitations. A brief history, technical overview and summary of preclinical and clinical studies of the KonaMedical Surround Sound(TM) system are presented. A literature search using the terms "renal denervation", "resistant hypertension" and "external ultrasound" was performed using PubMed, and references retrieved were selected based on relevancy and year of publication (date range 1991-2015). The Surround Sound(TM) system appears to be a promising approach to RDN which eliminates several of the factors currently limiting the intravenous approach. So far, it has demonstrated efficacy for reducing blood pressure in resistant hypertension patients with minimal adverse effects. Several double-blind, sham-controlled clinical trials are currently underway to confirm the validity of these findings.
EVALuna2:3851